Metode Pendidikan Karakter Melalui Pengajaran Moral Pencipta dan Sesama Manusia Anak Usia 5-6 Tahun di TK Islam Al-Izhar Cendekia Makassar - Islami, Andi Nur Maharani; Bachtiar, Muhammad Yusri; Yusran, Ramlah (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2024)
Character education is a form of effort and service in the field of education provided to children with the aim of helping their growth and development process physically and mentally. Character education refers to efforts in education that aim to support children's physical and mental development. This process is carried out by providing stimulation related to attitudes, knowledge, and basic skills combined with character education, which is designed to be appropriate to the context and environment in which the child is located. This study was conducted using a qualitative descriptive method approach to describe the observed phenomena in depth. The title raised by the researcher is